Analisis Pemberian Serbuk Jahe Merah, Kunyit, dan Temulawak Dengan Metode Insilico dan Invivo pada Ayam Broiler - Herawati .; Renanda Nur Al Jabbar; Yudit Oktanella (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2023)
This study aimed to eveluate effect of combination powder of red ginger (Zingiber officinale var. Rubrum), turmeric (Curcuma domestica), and temulawak (Curcuma xanthorrhiza) on the calculation of normal Liberkhun crypts by insilico and invivo methods. Molecular docking conducted in the pocket site of Interferon Lambda Receptor (IFN-λR) to modulate anti-inflammatory activity in chicken caecum. The study used 20 day old chickens (DOC) which were randomly grouped into 5 groups: negative control without treatment (P0) and powder addition group 0,5% (P1); 1%(P2); 1.5%(P3); 2%(P4). All chickens were reared for 35 days then chickens were euthanized using halal slaughter method and caecum organs were collected for histopathological observations. all active substances red ginger (gingerol, shogaol); turmeric (curcumin,tetrahydrocurcumin); and temulawak (demethoxycurcumin, bisdemethoxycurcumin) can bind to IFN-λR. Curcumin (-6.0 kcal/mol) have highest affinity values. Invivo treatment showed significant effect (p<0.05) on normal calculation of Liberkhun crypts due to tissue damage. Tukey's test confirmed that negative group was significantly different from P2, P3, and P4 with an average (4.35 ± 1.09b; 5.6 ± 1.54c; and 5.7 ± 1.78c). This research suggests that the addition of combination powder by 1,5% can potentially used for anti-inflamatory agent that confirmed by insilico method.